2013
DOI: 10.5507/bp.2013.065
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between reactive oxygen species production in human semen and sperm DNA damage assessed by Sperm Chromatin Structure Assay

Abstract: Aim. The aim of this prospective study was to find possible relationship between ROS production measured by chemiluminescence and flow cytometry in human semen and sperm DNA damage estimated by Sperm Chromatin Structure Assay. Methods. Study included 39 men from infertile couples and 23 fertile volunteers who served as a control group. Aliquot of neat semen was used for ROS detection by chemiluminescence. Aliquot of sperm suspension in phosphate buffered saline was used for the detection of ROS by flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
3
14
1
1
Order By: Relevance
“…Patients with oligozoospermia also displayed elevated SDF, in agreement with previous studies reporting significant negative correlations between sperm DNA damage and abnormal semen parameters, including low concentration (Fei et al, 2013;Novotny et al, 2013). The fact that patients with oligozoospermia frequently display reduced STL, high SDF and elevated aneuploidy rates suggests that diminished sperm concentration is symptomatic of meiotic and spermatogenic processes that are compromised on multiple levels.…”
Section: Article In Presssupporting
confidence: 85%
“…Patients with oligozoospermia also displayed elevated SDF, in agreement with previous studies reporting significant negative correlations between sperm DNA damage and abnormal semen parameters, including low concentration (Fei et al, 2013;Novotny et al, 2013). The fact that patients with oligozoospermia frequently display reduced STL, high SDF and elevated aneuploidy rates suggests that diminished sperm concentration is symptomatic of meiotic and spermatogenic processes that are compromised on multiple levels.…”
Section: Article In Presssupporting
confidence: 85%
“…The flow cytometry is used in the SCSA to measure stability of double-stranded sperm chromatin and evaluation of results without manual operation. 47 In the current study, there were 93.3% (27 of 30) and 76.7% (23 of 30) at 1 month SH treatment phase with a DFI greater than 20% and greater than 30%, respectively. In the current study, we found that subjects of SH treatment phase have a significantly higher percentage of sperm with fragmented DNA by using SCSA compared with recovery time.…”
Section: Discussionsupporting
confidence: 43%
“…High ROS concentrations in infertile men have been associated with DNA fragmentation and poor chromatin packing [Kodama et al 1997;Aitken and Krausz, 2001;Aitken et al 2003;Moustafa et al 2004;Cocuzza et al 2007;Desai et al 2009;Aitken and De Iuliis, 2010;Novotny et al 2013].…”
Section: Oxidative Stressmentioning
confidence: 99%